Nanotechnology and Racket Sports: - A Critical Review (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Ionizing radiations in the field of radiations are affecting the health depending on the doses of these radiations in human beings. Both the scientists as well as the common public are not showing deep concern in radiation exposure. Partly conflicting opinions from studies of low doses of radiations must be given attention. Advance technology in our everyday life is compelling us to have a concern on radiation exposure risks. In this direction the educational efforts might enlighten the path by creating awareness. The aim of this research paper is to create awareness of radiation exposure among all in the educational institutes and to suggest the need of framing a radiation safety curriculum or education program at education institutes, where students are learning and adopting the novel gadget and instruments etc. Providing the knowledge of radiation risks not only shows the risks of the radiation hazards but also develops the student's competency of decision making based on assessments.